Studies of evolutionary temperature adaptation: Muscle function and locomotor performance in Antarctic fish - Franklin, Craig E. (Clinical and Experimental Pharmacology and Physiology, 1998)
1. Studies of evolutionary temperature adaptation of muscle and locomotor performance in fish are reviewed with a focus on the Antarctic fauna living at subzero temperatures. 2. Only limited data are available to compare the sustained rind burst swimming kinematics and performance of Antarctic, temperate and tropical species. Available data indicate that low temperatures limit maximum swimming performance and this Is especially evident in fish larvae. 3. In a recent study muscle performance in the antarctic rock cod Notothenia coriiceps at 0°C was found to be sufficient to produce maximum velocities during burst swimming that were similar to those seen in the sculpin Myoxocephalus scorpius at 10°C, indicating temperature compensation of muscle and locomotor performance in the Antarctic fish. However, at 15°C, sculpin produce maximum swimming velocities greater than N. coriiceps at 0°C. 4. It is recommended that strict hypothesis-driven investigations using ecologically relevant measures of performance are undertaken to study temperature adaptation in Antarctic fish. Recent detailed phylogenetic analyses of the Antarctic fish fauna and their temperate relatives will allow a stronger experimental approach by helping to separate what is due to adaptation to the cold and what is due to phylogeny alone.